Answers

2015-05-19T16:14:51+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
We apply the conservation of energy principle here.  The electric field is conservative.

   The electric potential energy is converted into mechanical kinetic energy of the charged particle q.  The   change in PE when distance changes from r to 2 r :

         1/(4πε) * Q q [ 1/ r - 1/ (2r)  ]  = change in KE = 1/2 m v²

            v² = Qq / (4πε m)  * 1/ r
            v  = K / √r          let us say          K = √[Qq/(4πε m) ]

         v = velocity when the charge q is at a distance 2 r.
 
Change in linear momentum of the charge q = K m /√r

we know that the change in linear momentum = impulse = Force * Δt

So the impulse exerted by the external agent/force, on the Fixed charge Q, to keep it stationary, is equal to  k m /√r  = √ [Qqm / (4πε r) ]

So it is option B.
=====================
We can find the time duration to travel, we can find the velocity function and displacement of position of charge q at any time t.
      
   Let x = distance of q  from charge Q.  Let  v be the velocity of q at  distance x.

Change in PE when q moves from  x  to x+Δx      =  change in KE
       1/(4πε) * Q q [  1/(x+Δx) - 1/x ] = 1/2 m [ (v+Δv)² - v² ]
       - (Qq / (2πε m)) * Δx / [x(x+Δx)]  =  2 v Δv + (Δv)²
       - 2 K²  / [ x (x+Δx) ]  =  2 v  Δv / Δx  + Δv/Δx * Δv

 Taking limits as Δx  => 0 and Δv => 0 , we get
   =>  - 2 K² / x²  = 2 v dv / dx

 Integrating wrt x,  from x = r:
        =>  v² - 0  = 2 K² [ 1 / x  - 1 / r ]
                v² (x) = [ Qq/(2πε m) ] * [1 / x - 1/ r ]

When x = 2 r,
           v² (2r) =  Qq/(4πε m r)
         v (2 r) =  √ [ Qq / (4πε m r) ]



1 5 1
v² (x) = 2 K² [1/r - 1/x]
v² (s) = 2 K² [ s / ((r+s) r) ], where s = displacement from initial position of r.
v (s) = K ' √[ s/(r+s) ] where K ' = √ [Qq / (2πε m r) ]
ds/dt = K ' √[ s/(r+s) ]
√[ r /s + 1 ] ds = K ' dt
We need to find the integral to find displacement as a function of time.
K ‘ t = root[ s (s^2+r^2)/r^3 ] - Ln [ root(r^2+s^2) /r - root(s/r) ]
where K ' = √ [Qq / (2πε m r) ]
K ‘ t = 2 r { root(s’(1+s’)) - Ln [ root(1+s’) – root(s’) ] } after checking s = 0 to s and t from 0 to t. where K ' = √ [Qq / (2πε m r) ] and s’ = s/r
time for q to reach 2r from r : = (2r/K' ) * [ √2 - Ln (√2 - 1) ]